Effectiveness of Indirect Corrective feedback in English writing at the Faculty of English, Hanoi National University of Education - Nguyễn, Thị Khánh (2017)
Chapter 1–Literature review –synthesizes the results of other research that are relevant to this study. Chapter 2–Methodology –describes the methods utilized in the study. Chapter 3–Findings and Discussion –presents and analyses the collected data from students’ writing and questionnaires; provides the discussion based on the findings. Chapter 4–Recomendations–makes some suggestions for better use of teacher’s indirect corrective feedback to improve students’ writing accuracy and change their attitudes towards writing at FOE, HNUE